Method for detecting stability of latex and papermaking method
The viscosity changes of latex in metal cationic solutions of different concentrations are measured by a viscometer, which simplifies latex stability detection, solves the problems of cumbersome and insensitive detection in the prior art, and achieves rapid and accurate latex stability evaluation, which improves the Efficiency and product quality of papermaking process.
Patent Information
- Application Number
- CN202411302490.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the latex stability detection method is cumbersome, time-consuming and not sensitive enough to effectively characterize the stability of all latex application environments, resulting in unqualified paper product quality and malfunction of paper making equipment.
A viscometer was used to measure the viscosity changes of latex in metal cationic solutions of different concentrations, and the stability of latex was determined by exceeding the threshold, which simplified the detection process and expanded the scope of application.
It realizes fast, accurate and low-cost latex stability detection, reduces interference factors, improves detection sensitivity and applicability, and avoids paper product quality problems and papermaking equipment failures.
Smart Images

Figure CN119124931A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of papermaking, and in particular to a new method for on-site detection and screening of the stability of latex used in the field of papermaking, and application of the method in the field of papermaking. Background Art
[0002] Various latexes have very extensive and critical applications in the field of papermaking. They are usually added to pulp or applied to the surface of base paper as various additives and functional additives to achieve various expected functions. For example, styrene-butadiene latex has been used as a paper coating adhesive since the 1940s to make paper products have excellent pigment binding strength, wet friction strength, gloss, smoothness, printability, abrasion resistance, flex resistance, water resistance, or oil resistance.
[0003] But a very serious problem is that latex is often not used alone. For example, in papermaking technology, when latex is used to prepare paper pulp or prepare paper coating, in addition to containing latex, other components are often needed to be added in the paper pulp or coating for use, such as cellulose materials, inorganic pigments (such as calcium carbonate pigments), various organic and inorganic additives and salts. When these substances are mixed in water to form coatings, a certain amount of electrolyte will be formed. The latex used in the papermaking field is usually kept stable in the system by utilizing the negative charge carried on the surface of its colloidal particles. The electrolyte introduced by the above-mentioned substances is likely to cause the dispersion state of the latex to be damaged to varying degrees, and flocculation and demulsification occur, thereby causing coating accumulation, precipitation and other undesirable conditions. Once the situation of poor stability of this latex occurs in the papermaking process, it is very likely to cause serious problems, such as unqualified paper product quality, clogging, deposition and other failures in papermaking equipment, which seriously affect production and may even cause serious damage to papermaking equipment.
[0004] In order to avoid the above-mentioned problems, before each specific batch of latex is used to prepare pulp or formulate coatings, it must be pre-tested whether the latex can withstand the adverse effects of the electrolytes used in the formula on its stability. Specifically, it can be characterized by "metal cation stability (especially calcium ion stability)". Only latex that has been pre-tested to have qualified stability can be actually used to prepare pulp or formulate paper coatings.
[0005] The representative test method used to detect latex in the prior art is the sedimentation weighing method. For example, according to the petrochemical industry standard of the People's Republic of China (SH / T 1608-95; Determination of the stability of styrene-butadiene latex to calcium ions), Figure 1In the mixing device shown, calcium chloride solutions of different concentrations are added to the latex to be tested, and the solid precipitates thus generated are collected, washed, dried and weighed. The stability of the latex without adding calcium chloride is evaluated based on the measurement results of the final solid precipitates.
[0006] However, this detection technology has very significant defects. First, the detection of the above technology is too cumbersome and time-consuming, which seriously affects the efficiency of the papermaking process, and the steps are too complicated when switching different batches of latex; second, the adhesive itself will slowly produce dry glue coagulation when it comes into contact with air at room temperature, and this factor will cause serious interference to the detection result of the dry weight of the precipitated solid. When conducting the above detection, a blank experiment needs to be carried out at the same time to eliminate the interference factor, which further increases the complexity of the detection technology; third, the applicable conditions of this detection technology are too narrow, and it cannot characterize the latex stability (calcium ion stability) under all latex application environments, and the detection accuracy and sensitivity are still not satisfactory.
[0007] Therefore, there is an urgent need to develop a new latex stability detection technology in the art, which does not need to use the complicated and time-consuming precipitation-weighing operation in the prior art, can eliminate various interference factors, and preferably has a wider range of use environments, better accuracy, sensitivity, etc. In order to solve the above problems, various enterprises and research institutes in this field have invested a lot of research costs and energy in related research, but have never achieved the goal.
[0008] In response to this urgent problem, the applicant conducted a lot of in-depth research and developed the detection technology of the present invention, which can unexpectedly successfully solve the problem in the field. Summary of the invention
[0009] The first aspect of the present invention provides a method for detecting latex stability, the method comprising:
[0010] Step A: taking a plurality of parallel samples of the latex, wherein the plurality of parallel samples include parallel sample No. 0 and parallel samples No. 1 to No. N, where N is an integer of 3-20;
[0011] Step B: adding a sub-solution of a series of solutions containing at least one metal cation to each of the parallel samples No. 1 to No. N, respectively, wherein the series of solutions includes sub-solutions No. 1 to No. N, the sub-solutions No. 1 to No. N have the same volume and the concentration of the metal cations contained therein increases with a first increment, and adding the same volume of water to the parallel sample No. 0 as a blank parallel sample;
[0012] Step C: After adding the sub-solution or water, measure the viscosity of each parallel sample using a viscometer;
[0013] Step D: Determine the stability of the latex according to the sub-solutions corresponding to the parallel samples whose viscosity exceeds the threshold value, wherein the stability is represented by the concentration of metal cations in the corresponding sub-solutions.
[0014] According to one embodiment of the first aspect of the present application, the latex is selected from one or more of the following: styrene butadiene latex, carboxy styrene butadiene latex, styrene acrylic latex, polyacrylamide latex, silicone acrylic latex, acrylic latex, modified acrylic latex, polyvinyl acetate latex, vinyl acetate-ethylene latex, and epoxy latex.
[0015] According to another embodiment of the first aspect of the present application, the cation is a calcium ion, a magnesium ion, or a combination thereof.
[0016] According to another embodiment of the first aspect of the present application, the weight / volume ratio of each parallel sample to each corresponding sub-solution is 10:1-4:1 g / ml. According to another embodiment of the first aspect of the present application, the concentration of the cationic salt in the sub-solution is 0.1-20 wt%. According to another embodiment of the first aspect of the present application, the first increase is 0.5-2 wt%; according to another preferred embodiment of the first aspect of the present application, the first increase is 1 wt%.
[0017] According to another embodiment of the first aspect of the present application, the sub-solutions in the series of solutions have the same volume, the volume of the sub-solutions is 10 ml, the No. 1 sub-solution has the lowest metal cation concentration and its metal cation concentration is 1-5% by weight, and the metal cation concentration of the sub-solutions increases in an increment of 1% by weight.
[0018] According to another embodiment of the first aspect of the present application, in step C, the viscosity of each parallel sample is measured using a rotational viscometer, and the rotor speed of the rotational viscometer is 10-100 rpm.
[0019] According to another embodiment of the first aspect of the present application, the viscosity of each parallel sample is measured at a temperature of 25-45°C.
[0020] According to another embodiment of the first aspect of the present application, the threshold value is set to at least 1.5 times the viscosity of the blank parallel sample.
[0021] According to another embodiment of the first aspect of the present application, a stability prediction step is performed before step A, wherein the stability prediction step comprises taking a plurality of parallel prediction samples of the latex, wherein the plurality of parallel prediction samples comprises parallel prediction samples No. 1 to No. M, where M is an integer of 2-5, and M <N;
[0022] Add a sub-prediction solution from a series of prediction solutions containing at least one metal cation to one or more of the multiple parallel prediction samples simultaneously or successively. The series of prediction solutions includes sub-prediction solutions numbered from No. 1 to No. M. The sub-prediction solutions numbered from No. 1 to No. M have the same volume, and the concentration of the metal cation contained therein increases in a second increment, which is 2 - 10 times the first increment. Preferably, the second increment is 2 - 5 times the first increment;
[0023] Observe the flocculation and agitation changes of the parallel prediction samples after adding the series of prediction solutions containing metal cations to roughly predict the predicted concentration of the metal cation at which the latex viscosity exceeds the threshold, and select the concentration range of the metal cation in the No. 1 sub-prediction solution in the series of metal cation solutions according to this predicted concentration.
[0024] According to another embodiment of the first aspect of the present application, the sub-prediction solutions in the series of prediction solutions have the same volume, and the volume of each sub-prediction solution is 10 milliliters. The stability prediction step includes sub-step (i), and optionally includes one or more sub-steps (iia) or (iib):
[0025] (i) First, add the No. m sub-prediction solution (where m is an integer and 1 < m < M) with a cation concentration of 5 wt% to a parallel prediction sample of the latex, observe the flocculation and agitation changes of the parallel prediction sample after adding the series of prediction solutions containing metal cations, and roughly predict whether the latex viscosity exceeds the threshold;
[0026] (iia) If it is roughly predicted that the latex viscosity exceeds the threshold, then further add the No. m - 1 sub-prediction solution to another parallel prediction sample of the latex, and then observe the flocculation and agitation changes of the parallel prediction sample after adding the series of prediction solutions containing metal cations to roughly predict whether the latex viscosity exceeds the threshold;
[0027] (iib) If it is roughly predicted that the latex viscosity does not exceed the threshold, then further add the No. m + 1 sub-prediction solution to another parallel prediction sample of the latex, and then observe the flocculation and agitation changes of the parallel prediction sample after adding the series of prediction solutions containing metal cations to roughly predict whether the latex viscosity exceeds the threshold.
[0028] The second aspect of the present application provides a papermaking method, which includes:
[0029] Perform stability detection and screening on the latex by the method for detecting the stability of latex of the present invention; and
[0030] Add the screened latex to the pulp and / or apply it to the base paper.
[0031] The third aspect of the present application provides a paper product, which is manufactured by the papermaking method described above.
[0032] In the following detailed description section, the process and design of the present application are described in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram showing a sedimentation-weighing method detection device used in the prior art to detect latex stability;
[0034] Figure 2 A schematic diagram showing a device for mixing parallel samples of latex and metal cation sub-solutions in the method of the present invention is shown;
[0035] Figure 3A and Figure 3B Schematic diagrams of viscosity detection devices for detecting latex stability according to the present invention are respectively shown;
[0036] Figure 4 The solid residue mass measured by the sedimentation-solid weighing method for two different latexes is shown;
[0037] Figure 5 The solid residue mass measured by the sedimentation-solid weighing method for different batches of the same latex is shown;
[0038] Figure 6 The viscosity measurement results of two different latexes using the method of the present invention are shown;
[0039] Figure 7 The results of viscosity measurements of different batches of the same latex using the method of the present invention are shown. DETAILED DESCRIPTION
[0040] It should be emphasized that what is shown in the drawings and described below are only some specific embodiments of the present invention, and the protection scope of the present invention is not limited to these specific embodiments. The protection scope of the present invention is defined by the claims of the present invention, and may include any technical solution within the scope of the claims, including but not limited to further improvements and substitutions to these specific embodiments.
[0041] According to one embodiment of the present application, the method for detecting latex stability provided by the present invention comprises the following steps:
[0042] Step A: taking a plurality of parallel samples of the latex, wherein the plurality of parallel samples include parallel sample No. 0 and parallel samples No. 1 to No. N, where N is an integer of 3-20;
[0043] Step B: adding a sub-solution of a series of solutions containing at least one metal cation to each of the parallel samples No. 1 to No. N, respectively, wherein the series of solutions includes sub-solutions No. 1 to No. N, the sub-solutions No. 1 to No. N have the same volume and the concentration of the metal cations contained therein increases with a first increment, and adding the same volume of water to the parallel sample No. 0 as a blank parallel sample;
[0044] Step C: After adding the sub-solution or water, measure the viscosity of each parallel sample using a viscometer;
[0045] Step D: Determine the stability of the latex according to the sub-solutions corresponding to the parallel samples whose viscosity exceeds the threshold value, wherein the stability is represented by the concentration of metal cations in the corresponding sub-solutions.
[0046] According to one embodiment of the present application, before each use of a new latex in the papermaking process, or before each use of different batches of the same latex, it is necessary to use the above-mentioned method of the present invention to detect the stability of the latex. After the test confirms that the stability of the latex is qualified, more specifically, it is to determine that after a specific amount of metal cations is added to the latex sample, the viscosity will not increase to a level exceeding a threshold value, and then the specific type and / or specific batch of latex can be used in the papermaking process.
[0047] According to an exemplary embodiment of the present application, in step A, a plurality of parallel samples of the latex are taken, the plurality of parallel samples include parallel samples No. 1 to No. N, N is an integer of 3-20, preferably N is an integer of 3-8, according to a specific embodiment of the present application, 3, 4, 5 or 6 parallel samples are taken. The plurality of parallel samples also include parallel sample No. 0.
[0048] According to an exemplary embodiment of the present application, the latex of the present invention includes latex that can be used in the papermaking field, examples of which include styrene butadiene latex, carboxylated styrene butadiene latex, styrene acrylic latex (for example, latex prepared by copolymerization of styrene, acrylate and other optional comonomers), polyacrylamide latex, silicone acrylic latex, acrylic latex, modified acrylic latex, polyvinyl acetate (PVAc) latex, vinyl acetate ethylene (VAE) latex, epoxy latex, and the like.
[0049] According to an exemplary embodiment of the present application, based on the total weight of the latex, the solid content of the latex is 30-60% by weight, preferably 50-60% by weight.
[0050] According to an exemplary embodiment of the present application, each latex parallel sample (parallel sample No. 1 to No. N, and parallel sample No. 0) has the same volume or weight as each other, for example, the weight of each latex parallel sample can be or 10-100 grams, preferably 50-60 grams, for example, according to a preferred embodiment of the present application, the weight of each latex parallel sample is 50 grams.
[0051] Then, in step B, a sub-solution of a series of solutions containing at least one metal cation is added to each of the parallel samples No. 1 to No. N, respectively, wherein the series of solutions includes sub-solutions No. 1 to No. N, and the concentration of the metal cations contained in the sub-solutions No. 1 to No. N increases in a first increment. That is, the number of sub-solutions included in the metal cation series solution is N, corresponding to the parallel latex samples No. 1 to No. N, each sub-solution corresponds to the parallel latex sample with the corresponding number, and the concentration of the N sub-solutions of the metal cation gradually increases, from when each sub-solution is mixed with the corresponding parallel latex solution (e.g., the 1st sub-solution with the 1st parallel latex solution, the 2nd sub-solution with the 2nd parallel latex solution, ... the Nth sub-solution with the Nth parallel latex solution) (e.g., the sub-solution is added to the parallel latex solution), the metal cations with gradually increasing concentrations are added to each parallel latex sample. In addition, the parallel latex sample No. 0 is mixed with water (preferably deionized water), and then used as a blank parallel sample, and the threshold is determined based on the viscosity of the parallel sample.
[0052] According to one embodiment of the present application, the metal cation is calcium ion, magnesium ion, or a combination thereof. The corresponding anion can be an anion that makes the above metal cation have sufficiently high water solubility and does not have a negative impact on various additives and / or processes of papermaking process, for example, selected from one or more of the following: chloride ion, sulfate, phosphate, nitrate, etc. According to a preferred embodiment, the series of solutions of the metal cation is calcium chloride aqueous solution.
[0053] According to one embodiment of the present application, each sub-solution of the metal cation has the same volume, specifically, the volume of each sub-solution is 1-50 ml, preferably 5-20 ml, and most preferably 8-10 ml. According to another embodiment of the present application, the volume of water mixed with the No. 0 parallel sample is the same as the volume of the above-mentioned metal cation sub-solution.
[0054] According to one embodiment of the present application, the concentration of each sub-solution of metal cations increases within the above-defined range, wherein the first sub-solution has the lowest concentration (weight percentage concentration of cationic metal salt), and the Nth sub-solution has the highest concentration. For example, the concentration of the first sub-solution is 0.1-5% by weight, preferably the concentration of the first sub-solution is 1-5% by weight, more preferably 1% by weight, 2% by weight, 3% by weight, 4% by weight or 5% by weight. The concentration of the Nth sub-solution is up to 20% by weight, preferably less than 12% by weight, and more preferably 7-11% by weight.
[0055] According to one embodiment of the present application, the concentration increase between any two adjacent sub-solutions (for example, the concentration difference between sub-solution No. 1 and sub-solution No. 2) is uniform, for example, the concentration increase (first increase) can be 0.5-2 weight %, preferably the first increase is 0.8-1.5 weight %, and most preferably the first increase is 1 weight %.
[0056] According to one embodiment of the present application, the ratio (weight ratio) of each of the No. 1 to No. N latex parallel samples to each corresponding metal cation sub-solution is 10: 1-4: 1, preferably 5: 1-4: 1. According to another embodiment of the present application, the ratio (weight ratio) of the No. 0 parallel sample and the water mixed therewith is equal to the ratio (weight ratio) of the above-mentioned No. 1 to No. N latex parallel samples to each corresponding metal cation sub-solution.
[0057] According to one embodiment of the present application, the solvent used in the latex parallel sample and the metal cation sub-solution is an aqueous solvent, preferably water, and more preferably deionized water.
[0058] According to one embodiment of the present application, for parallel latex samples No. 1 to No. N, the metal cation sub-solution is slowly added dropwise to the parallel latex samples, and for parallel latex sample No. 0, water is slowly added dropwise thereto. For example, the metal cation sub-solution or water is added dropwise using a dropper, a pipette or a titration gun. According to one embodiment of the present application, while the parallel latex samples are continuously stirred, the metal cation sub-solution or water is added dropwise over a period of 10 seconds to 10 minutes, for example, the addition time is 30 seconds to 5 minutes, preferably 60-90 seconds.
[0059] According to an exemplary embodiment of the present application, step B can be carried out at a temperature of 25-45° C., preferably 30-35° C. According to another embodiment of the present application, after the addition of the metal cation sub-solution or water, the mixture of the latex parallel sample and the metal cation sub-solution, or the mixture of the No. 0 latex parallel sample and water is stirred and mixed for a period of time, for example, 10 seconds to 10 minutes, preferably for another 1-5 minutes. The mixing can be stirred using a magnetic stirrer or a mechanical stirrer, and the rotation speed can be set to 50-1000rpm, preferably 200-300rpm.
[0060] According to an exemplary embodiment of the present application, step B can be carried out in a mixing device having a mechanical stirrer or a magnetic stirrer, for example, Figure 2 The mixing device is shown.
[0061] According to one embodiment of the present application, after each latex parallel sample is mixed with the corresponding metal cation sub-solution or water in step B, the viscosity of the resulting mixture is measured using a viscometer in step C. A rotational viscometer can be used to measure the viscosity. According to one embodiment of the present application, the patent rotation speed used is selected according to the viscosity of the sample to be tested (for example, the sample viscosity estimated based on experience). According to one embodiment of the present application, the viscosity of the latex parallel samples after mixing with the metal cation solution is 0-500 centipoise, for example, 10-350 centipoise, preferably 200-320 centipoise, and accordingly the viscosity detection is carried out at a rotor speed of 10-100rpm, preferably when the viscosity detection is carried out, the rotor speed of the viscometer is 10-20rpm, and most preferably 10-15rpm.
[0062] According to one embodiment of the present application, the viscosity of each mixture is measured at a temperature of 25-45° C., preferably at a temperature of 30-40° C. According to one embodiment of the present application, a portion or all of each mixture is transferred to a viscometer (e.g. Figure 3A and Figure 3B The viscosity of each mixture was measured using a DV2TLVJ0 viscometer as shown above at the rotor speed and monitoring temperature.
[0063] In step D, it is determined whether the viscosity of each mixture measured in step C exceeds a preset viscosity threshold. If the viscosity of all the mixtures tested does not exceed the viscosity threshold, it is considered that the latex samples tested are stable under the condition of the amount of cation added. If the viscosity of one or more mixtures (a mixture of a parallel sample of latex and a sub-solution of a metal cation) is equal to or greater than the above threshold, for example, the nth parallel sample (n is an integer and 1≤n≤N) observes a viscosity equal to or greater than the threshold, then the metal cation concentration (expressed in weight percentage) contained in the metal cation sub-solution corresponding to the nth parallel sample is used to characterize the stability of the latex. For example, if the metal cation concentration of the nth metal cation sub-sample is 6% by weight, it is considered that the latex stable concentration is <6%. In the present invention, this nth parallel sample is referred to as a "viscosity super-threshold point" or a "viscosity inflection point".
[0064] According to one embodiment of the present application, the "threshold value" is set to be significantly higher than the viscosity of the blank latex parallel sample (that is, the viscosity of the mixture of the No. 0 latex parallel sample and water described above measured under the above-mentioned viscometer and detection conditions, for example, 1.5 times the viscosity of the blank parallel sample, or 3 times the viscosity of the blank parallel sample, preferably 5 times the viscosity of the blank parallel sample.
[0065] According to a specific embodiment of the present application, the weight of each parallel sample of the latex (including parallel sample No. 0 and parallel samples No. 1 to No. N) is 50 grams, each sub-solution in the metal cation series solution and the water mixed with the parallel sample No. 0 of latex have the same volume, preferably a volume of 10 ml, the metal cation concentration of the sub-solutions increases uniformly, the first increase is 1 weight%, the metal cation concentration of the sub-solution with the lowest concentration in the series of solutions (sub-solution No. 1) is 1-4 weight%, preferably 1 weight% or 4 weight%, and the concentration of the sub-solution with the highest concentration in the series of solutions is 7 weight%, 8 weight%, 9 weight%, 10 weight%, 11 weight% or 12 weight%.
[0066] According to one embodiment of the present application, a stability prediction step is performed before step A to roughly determine the stability range of the latex, thereby further predicting the location of the viscosity inflection point, thereby significantly reducing the number of parallel latex samples and cationic sub-solutions required for testing (reducing the value of N).
[0067] For example, the stability prediction step includes roughly adding a solution containing cations to the latex and observing the formation of flocculation with the naked eye, thereby roughly determining an approximate range including the viscosity inflection point (threshold), and then performing a subsequent stability test according to the method of the present invention, and selecting the number and / or concentration range of the metal cation series solutions based on the above approximate range.
[0068] According to an exemplary embodiment of the present application, the prediction step is performed in the following manner: taking a plurality of parallel prediction samples of the latex, the plurality of parallel prediction samples including parallel prediction samples No. 1 to No. M, M is an integer of 2-5, and M <N;
[0069] Adding a sub-prediction solution of a series of prediction solutions containing at least one metal cation to one or more of the plurality of parallel prediction samples simultaneously or successively, the series of prediction solutions comprising sub-prediction solutions No. 1 to No. M, the sub-prediction solutions No. 1 to No. M having the same volume and the concentration of the metal cations contained therein increases with a second increase, the second increase being 2-10 times the first increase, preferably the second increase being 2-5 times the first increase;
[0070] Observe the changes in flocculation and agitation of parallel prediction samples after adding a series of prediction solutions of metal cations to roughly predict the predicted metal cation concentration at which the latex viscosity exceeds the threshold, and select the metal cation concentration range of the first sub-prediction solution in the series of metal cation solutions based on the predicted concentration.
[0071] According to one embodiment of the present application, each parallel prediction sample has the same weight, such as 10-100 grams, preferably 50-60 grams. According to one embodiment of the present application, each sub-prediction solution has the same volume, such as 2-20 milliliters, preferably 10-15 milliliters.
[0072] The aforementioned simultaneous or sequential addition of a sub-prediction solution in a series of prediction solutions containing at least one metal cation to one or more of the plurality of parallel prediction samples includes two operation modes.
[0073] In the first operation mode, a parallel prediction sample is first selected, a sub-prediction solution with a "medium metal cation concentration" is added thereto, and then a sub-prediction solution with a lower or higher metal cation concentration is added according to the situation. The above-mentioned sub-prediction solution with a "medium metal cation concentration" means that the sub-prediction solution is neither the one with the highest metal cation concentration nor the one with the lowest metal cation concentration in the series of prediction solutions.
[0074] According to an exemplary embodiment of the present application, the sub-prediction solutions in the series of prediction solutions have the same volume, and the volume of the sub-prediction solutions is 10 ml. The stability prediction step includes sub-step (i), and optionally includes one or more sub-steps (iia) or (iib):
[0075] (i) First, add a sub-prediction solution No. m (m is an integer, and 1 < m < M) with a cation concentration of 5% by weight to a parallel prediction sample of the latex, observe the flocculation and agitation changes of the parallel prediction sample after adding a series of prediction solutions of metal cations, and roughly predict whether the latex viscosity exceeds the threshold;
[0076] (iia) If it is roughly predicted that the latex viscosity exceeds the threshold, then further add the sub-prediction solution No. m - 1 to another parallel prediction sample of the latex, and then observe the flocculation and agitation changes of the parallel prediction sample after adding a series of prediction solutions of metal cations to roughly predict whether the latex viscosity exceeds the threshold;
[0077] (iib) If it is roughly predicted that the latex viscosity does not exceed the threshold, then further add the sub-prediction solution No. m + 1 to another parallel prediction sample of the latex, and then observe the flocculation and agitation changes of the parallel prediction sample after adding a series of prediction solutions of metal cations to roughly predict whether the latex viscosity exceeds the threshold.
[0078] According to an exemplary embodiment of the present application, first add 10 mL of a cationic brine solution (such as an aqueous CaCl2 solution) with a concentration of 5% by weight to a parallel prediction sample of the latex (50 g). When it is observed under stirring conditions that the rotation speed of the stirring slows down, flocculation occurs, foam is generated, or the wall is adhered due to a significant increase in viscosity, the viscosity inflection point is judged accordingly; or continue to take a brand-new parallel prediction sample of the latex (50 g), add a cationic brine solution with a lower concentration (such as an aqueous CaCl2 solution) thereto, preferably add a cationic brine solution with a concentration of 3%, and then observe whether viscosity changes (judged according to the change in the stirring rotation speed), flocculation, foam generation, or wall adhesion occur again.
[0079] If the phenomenon that the rotation speed of the stirring slows down, flocculation occurs, foam is generated, or the wall is adhered due to a significant increase in viscosity does not occur, then the general stability range is judged accordingly; or continue to take a brand-new parallel prediction sample of the latex (50 g), add a cationic brine solution with a higher concentration (such as an aqueous CaCl2 solution) thereto, preferably add a cationic brine solution with a concentration of 10%, and then observe whether viscosity changes (judged according to the change in the stirring rotation speed), flocculation, foam generation, or wall adhesion occur again.
[0080] Through the above prediction steps, roughly predict the approximate range of the inflection point to reduce the number of parallel samples in the subsequent step B.
[0081] In the second operation mode, a sub-prediction solution of a series of prediction solutions containing at least one metal cation is added to each of the multiple parallel prediction samples at the same time, and then the state of each mixture (a mixture of parallel prediction samples and sub-prediction solutions) is observed to see whether viscosity changes (determined by changes in stirring speed), flocculation, foaming or wall hanging occurs, thereby roughly predicting the approximate range of the inflection point.
[0082] According to an exemplary embodiment of the present application, the prediction step can be performed in the following manner: add (for example, using a dropper or titration device) metal cation solutions (for example, calcium chloride aqueous solution) with concentrations of 1 wt%, 5 wt%, 10 wt% and 15 wt% to the latex respectively, the ratio of latex to metal cation solution is as described above, and observe with the naked eye whether the latex after adding the cation solution produces obvious flocculation, so as to roughly determine the interval (expressed in terms of metal cation concentration) including the latex viscosity inflection point (threshold). According to a preferred specific embodiment of the present application, the volume of each parallel solution in the latex solution is 50 grams, and the volume of each sub-solution in the cation solution is 10 milliliters. At this time, it is set that the qualified latex has a stability of at least 5 wt%, that is, for qualified latex that meets the requirements, its parallel solution will not have a "viscosity inflection point" after mixing with at least 5 wt% of the sub-solution.
[0083] The advantage of the present invention is that by using a viscometer to measure the viscosity inflection points of parallel latex solutions after adding a series of solutions of metal cations of different concentrations, the stability of latex samples provided by different suppliers and / or different batches of latex samples provided by the same supplier can be accurately and sensitively detected, thereby achieving convenient, fast, low-cost, interference-free and highly accurate detection.
[0084] Example
[0085] The preferred embodiments of the present invention are specifically listed in the following examples, but it should be understood that the protection scope of the present application is not limited thereto. Any equivalent changes or modifications made according to the essence of the present application should be included in the protection scope of the present application.
[0086] The water used in the following examples is deionized water, and all calcium chloride used is commercially purchased analytically pure products, which are used directly without further purification and treatment. The latex sample A used in the examples is styrene butadiene latex purchased from Jinma Chemical, with a solid content of 50 wt% ± 2% and a Tg of 0-5°C; the latex sample B used in the examples is styrene butadiene latex purchased from Trinseo, with a solid content of 54 wt% ± 2% and a Tg of 14-20°C.
[0087] Comparative Example 1
[0088] First, in Comparative Example 1, according to the steps specified in SH / T 1608-2014, Figure 1 The device shown in the figure was used to sample latex A (including two different batches of samples from the same supplier) and latex B at different times for sedimentation-solid weighing method testing. Specifically, the steps specified in SH / T 1608-2014 are as follows:
[0089] Place a 500 ml beaker in a water bath adjusted to 25°C ± 3°C (for clarity, Figure 1 The water bath device is omitted). The latex sample to be tested is filtered using an 80-mesh stainless steel filter screen, and then 200 g ± 0.2 g of the latex sample is weighed and added into a beaker.
[0090] Insert the stirring piece into the sample to be tested in the beaker, the lower end of the blade is about 3mm from the bottom of the beaker, adjust the stirring speed to 500r / min±10r / min, use a burette to uniformly drip 50ml of a calcium chloride solution with a concentration of 1% by weight along the edge of the blade within 5.5min±0.5min, and continue stirring for 2 minutes after the addition is completed. Use a stainless steel mesh screen that has been weighed in advance (accurate to 0.0001g) to filter the material in the beaker, flush the residual materials on the beaker and the blade into the net together with water, and then slowly and thoroughly rinse the condensate in the net with water. Place the screen in a vacuum oven, adjust the temperature to 120℃±2℃, and the vacuum degree to 0.03Mpa±0.005Mpa. Take out the screen after drying for 30min, cool to room temperature in a desiccator, and weigh to an accuracy of 0.0001g.
[0091] Calcium ion stability (%) = (dry weight of coagulant / dry weight of latex) * 100
[0092] The test results are shown in Table 1 and the results are plotted in Figure 4 and 5 .
[0093] Table 1 Comparison of different latexes and different batches of Type A latex
[0094]
[0095] From Table 1 above and Figure 4 and 5 It can be seen that when calcium chloride is added at a concentration of 1 wt %, the amount of solid precipitate (screen residue) formed is very small, that is to say, under the condition of adding 1 wt % calcium chloride, the latex samples to be tested all show qualified stability.
[0096] If the stability of the latex sample needs to be further tested, the above steps need to be repeated, and calcium chloride solution with increasing concentrations is added to the parallel latex samples to be tested, and the amount of solid precipitate (screen residue) formed is tested. This will be a time-consuming and complicated process, which will cause great trouble to the latex sample testing process and even the papermaking process, and may even affect the smooth progress of the papermaking process, greatly increasing its cost.
[0097] Example 1
[0098] In this embodiment, according to the steps described below, use Figure 2 The mixing device shown and Figure 3A and 3B The viscometer shown was used to measure the viscosity of latex A and latex B under different calcium chloride addition conditions.
[0099] Specifically, we first make a rough prediction of the inflection point range in the following manner: take 4 portions of 50 grams each of latex type A or latex type B, add 10 ml of an aqueous calcium chloride solution with a concentration of 1 weight %, 5 weight %, 10 weight % and 15 weight % respectively, and observe the flocculation formation in the latex with the naked eye. It was found that both latexes remained stable at least at 5 weight %, and both produced flocculation after the addition of 10 weight % calcium chloride solution.
[0100] Through the above rough prediction steps, it was determined that both latexes A and B remained stable at least at 5 wt %, so the minimum concentration of calcium chloride solution was selected as 5 wt % in the following experiments.
[0101] Filter the latex A or B with a 325-mesh filter in advance, and then accurately weigh 8 samples of each latex, each sample is 50.0 grams. The volume of each sub-solution in the corresponding calcium chloride series solution is 10 ml, and the weight percentage concentration is 0% (blank experiment), 5%, 6%, 7%, 8%, 9%, 10%, and 11%.
[0102] Add one portion of the sample to a 500 ml beaker, place the beaker on a magnetic heating plate with a temperature control sleeve, place a type A magnetic rotor wrapped in tetrafluoroethylene into the beaker, start magnetic stirring, set the speed to gear 2 (the speed of the magnetic rotor is about 200-300rpm at this time, depending on the viscosity of the sample) and raise the temperature to 30°C. Use a titration gun to slowly drip CaCl2 solution (one portion of the solution) into the stirred sample, and control the slow injection to complete within 1 minute. After the addition is completed, keep the material in the beaker stirring at 30°C for 2 minutes. Then use a pipette to transfer 7ml of the sample solution and add it to Figure 3A The viscosity test was performed in the DV2TLVJ0 viscometer sample tank at a constant temperature of 30° C. The viscometer parameters were set as follows: rotor model SC4-21 speed: 10 rpm temperature: 30° C.
[0103] Repeat the above experimental process, adding a portion of CaCl2 sub-solution of different concentrations each time (the blank experiment is to add the same volume of deionized water) to test the sample viscosity.
[0104] In this embodiment, the threshold is set to twice the viscosity of the blank test latex (the threshold for latex A is 58.2 cP, and the threshold for latex B is 26.2 cP). When the viscosity of the experimental sample exceeds the threshold, it is determined that the viscosity inflection point has been reached.
[0105] The test results are summarized in Table 2 and Figure 6 .
[0106] Table 2 Stability test results of latex provided by different suppliers
[0107]
[0108] From Table 2 and Figure 6 The experimental results show that the calcium chloride stability of latex A is <6%, and the calcium chloride stability of latex B is <10%.
[0109] Example 2
[0110] In this embodiment, according to the steps described below, use Figure 2 The mixing device shown and Figure 3A and 3B The viscometer shown in the figure measures the viscosity of different batches of A latex under different calcium chloride addition conditions. In this example, batch 1 (B1), batch 2 (B2) and batch 3 (B3) of A latex were tested.
[0111] Specifically, firstly, a rough prediction of the inflection point range is made as follows: 2 portions of 50 grams each are taken from batches B1, B2 and B3 of latex type A.
[0112] First, 10 ml of 5 wt % calcium chloride aqueous solution was added to each of the samples of batches B1, B2 and B3. It was observed that the latex of batches B1 and B3 remained stable, while the latex of batch B2 flocculated.
[0113] Then, 10 ml of 10 wt % calcium chloride aqueous solution was added to another fresh sample of batches B1 and B3, and flocculation was observed.
[0114] To another fresh sample of batch B2, 10 ml of a 3 wt % calcium chloride aqueous solution was added. It was observed that the latex of batch B2 remained stable without flocculation.
[0115] Through the above rough prediction steps, it is determined that the viscosity inflection point of batches B1 and B3 of type A latex is approximately between 5-10 weight %, and the viscosity inflection point of batch B2 is approximately around 4-5 weight %. Therefore, in the following experiments, the minimum concentration of calcium chloride solution is selected as 4 weight %.
[0116] Different batches of type A latex were pre-filtered with a 325-mesh filter, and then 5 samples of each type of latex were accurately weighed, each sample was 50.0 grams. The volume of each sub-solution in the corresponding calcium chloride series solution was 10 ml, and the weight percentage concentrations were 0% (blank experiment), 4%, 5%, 6%, and 7%.
[0117] Add one portion of the sample to a 500 ml beaker, place the beaker on a magnetic heating plate with a temperature control sleeve, place a type A magnetic rotor wrapped in tetrafluoroethylene into the beaker, start magnetic stirring, set the speed to gear 2 (the speed of the magnetic rotor is about 200-300rpm at this time, depending on the viscosity of the sample) and raise the temperature to 30°C. Use a titration gun to slowly drip CaCl2 solution (one portion of the solution) into the stirred sample, and control the slow injection to complete within 1 minute. After the addition is completed, keep the material in the beaker stirring at 30°C for 2 minutes. Then use a pipette to transfer 7ml of the sample solution and add it to Figure 3A The viscosity test was performed in the DV2TLVJ0 viscometer sample tank at a constant temperature of 30° C. The viscometer parameters were set as follows: rotor model SC4-21 speed: 10 rpm temperature: 30° C.
[0118] Repeat the above experimental process, adding a portion of CaCl2 sub-solution of different concentrations each time (the blank experiment is to add the same volume of deionized water) to test the sample viscosity.
[0119] In this embodiment, the threshold is set to twice the viscosity of the blank test latex (the threshold for B1 batch latex is 58.2 cP, the threshold for B2 batch latex is 73.6 cP, and the threshold for B3 batch latex is 52.2 cP). When the viscosity of the experimental sample exceeds the threshold, it is determined that the viscosity inflection point has been reached.
[0120] The test results are summarized in Table 3 and Figure 7 .
[0121] Table 3 Stability test results of different batches of latex A
[0122]
[0123] From Table 3 and Figure 7 From the experimental results, we can see that the viscosity inflection points of the three different batches of latex A are 6%, 5% and 6% respectively, among which the viscosity change rate of B1 is higher than that of B3. Therefore, the calcium ion stability of these three batches of samples is in the order of B3>B1>B2.
[0124] From the above experimental comparison, it can be seen that the method of the embodiment of the present invention can detect the stability of the latex sample more quickly and conveniently than the comparative example, while also achieving the advantages of cost saving, no interference and high accuracy.
Claims
1. A method for detecting latex stability, the method comprising: Step A: taking a plurality of parallel samples of the latex, wherein the plurality of parallel samples include parallel sample No. 0 and parallel samples No. 1 to No. N, where N is an integer of 3-20; Step B: adding a sub-solution of a series of solutions containing at least one metal cation to each of the parallel samples No. 1 to No. N, respectively, wherein the series of solutions includes sub-solutions No. 1 to No. N, the sub-solutions No. 1 to No. N have the same volume and the concentration of the metal cations contained therein increases with a first increment, and adding the same volume of water to the parallel sample No. 0 as a blank parallel sample; Step C: After adding the sub-solution or water, measure the viscosity of each parallel sample using a viscometer; Step D: Determine the stability of the latex according to the sub-solutions corresponding to the parallel samples whose viscosity exceeds the threshold value, wherein the stability is represented by the concentration of metal cations in the corresponding sub-solutions.
2. The method according to claim 1, characterized in that The latex is selected from one or more of the following: styrene-butadiene latex, carboxylated styrene-butadiene latex, styrene-acrylic latex, polyacrylamide latex, silicone-acrylic latex, acrylic latex, modified acrylic latex, polyvinyl acetate latex, vinyl acetate-ethylene latex, and epoxy latex.
3. The method according to claim 1, characterized in that The cation is a calcium ion, a magnesium ion, or a combination thereof; The weight ratio of each parallel sample to each corresponding sub-solution was 10:1-4:1; The concentration of the cationic salt in the sub-solution is 0.1-20 wt %; The first increase is 0.5-2% by weight.
4. The method according to claim 1, characterized in that The sub-solutions in the series of solutions have the same volume, which is 10 ml. Sub-solution No. 1 has the lowest metal cation concentration and its metal cation concentration is 1 wt % to 5 wt %. The metal cation concentration of the sub-solutions increases in increments of 1 wt %.
5. The method according to claim 1, characterized in that In step C, the viscosity of each parallel sample is measured using a rotational viscometer, the rotor speed of the rotational viscometer being 10-100 rpm; and the viscosity of each parallel sample is measured at a temperature of 25-45°C.
6. The method according to claim 1, characterized in that The threshold was set to be at least 1.5 times the viscosity of the blank replicate.
7. The method according to claim 1, characterized in that Before step A, a stability prediction step is performed, wherein the stability prediction step comprises taking a plurality of parallel prediction samples of the latex, wherein the plurality of parallel prediction samples comprises parallel prediction samples No. 1 to No. M, where M is an integer of 2-5, and M <N; Adding a sub-prediction solution of a series of prediction solutions containing at least one metal cation to one or more of the plurality of parallel prediction samples simultaneously or successively, the series of prediction solutions comprising sub-prediction solutions No. 1 to No. M, the sub-prediction solutions No. 1 to No. M having the same volume and the concentration of the metal cations contained therein increases with a second increase, the second increase being 2-10 times the first increase, preferably the second increase being 2-5 times the first increase; Observe the changes in flocculation and agitation of parallel prediction samples after adding a series of prediction solutions containing metal cations, to roughly predict the metal cation prediction concentration at which the latex viscosity exceeds the threshold, and select the metal cation concentration range of the No. 1 sub-prediction solution in the series of metal cation solutions based on this predicted concentration.
8. The method according to claim 7, characterized in that The sub-prediction solutions in the series of prediction solutions have the same volume, and the volume of each sub-prediction solution is 10 mL. The stability prediction step includes sub-step (i), and optionally includes one or more sub-steps (iia) or (iib): (i) First, add the No. m sub-prediction solution (where m is an integer and 1 < m < M) with a cation concentration of 5 wt% to a parallel prediction sample of the latex, observe the changes in flocculation and agitation of the parallel prediction sample after adding the series of prediction solutions containing metal cations, and roughly predict whether the latex viscosity exceeds the threshold; (iia) If it is roughly predicted that the latex viscosity exceeds the threshold, then further add the No. m - 1 sub-prediction solution to another parallel prediction sample of the latex, and then observe the changes in flocculation and agitation of the parallel prediction sample after adding the series of prediction solutions containing metal cations, to roughly predict whether the latex viscosity exceeds the threshold; (iib) If it is roughly predicted that the latex viscosity does not exceed the threshold, then further add the No. m + 1 sub-prediction solution to another parallel prediction sample of the latex, and then observe the changes in flocculation and agitation of the parallel prediction sample after adding the series of prediction solutions containing metal cations, to roughly predict whether the latex viscosity exceeds the threshold.
9. A papermaking method, the method comprising: Performing stability detection and screening on the latex by the method according to any one of claims 1 - 8; And Adding the screened latex to the pulp and / or applying it to the base paper.
10. A paper product manufactured by the method according to claim 9.
